Biotechnology : Applying the Genetic Revolution - David P. Clark and Nanette J. Pazdernik (Academic Press/Elsevier, 2009)
Helps readers understand what molecular biotechnology actually is as a scientific discipline, how the research in this area is conducted, and how this technology may impact the future. This text focuses on modern biotechnology with a molecular foundation. It also features clear, color illustrations of key topics and concepts.